A Comparative Study of the Influence of Different Types of Polymers on Viscosity Index and Pour Point of Iraqi Base Oils - Abdul-saheb, Rusul F.; Mohammed, Muhanned A. (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
In this study, the effects of blending the un-branched acrylate polymer known as Poly (n-decyl acrylate), and the branched acrylate polymer known as Poly (iso-octyl acrylate), on the viscosity index (VI), and the pour point of the Iraqi base stocks 40, and 60 respectively, were investigated. Toluene was used as a carrier solvent for both polymer types. The improvement level of oils (VI, & pour point) gained by blending the oil with the acrylate derived polymers was compared with the values of (VI, and pour point) gained by blending the oil with a commercial viscosity index, and pour point improver. The commercial lubricant additive was purchased and used by Al-Daura Refineries. It consisted of an un-known olefin copolymer dissolved in an un-known carrier solvent. All polyacrylate derivatives and the commercial lubricant additive named HITEC5748 were blended with each type of oil in weight percentage of (2, 4, 6, 8, & 10) wt. %. The result of the study was that the improvement in the viscosity index and the pour point of both base stock types was higher when using the polyacrylate derivatives than when using the commercial olefin copolymer additive.